Metal-organic hybrids of 1,3,5-tris(4-pyridylsulfanylmethyl)-2,4,6-trimethylbenzene with mercuric halides - PrakashaReddy, Jayarama; Pedireddi, Venkateswara Rao (European Journal of Inorganic Chemistry, 2007)
Synthesis and solid-state structure elucidation of metal-organic hybrids of 1,3,5-tris(4-pyridylsulfanylmenthyl)-2,4,6-trimethylbenzene with Hg(II) halides (HgCl(2), HgBr(2), and HGI(2)) are reported. In the metal-hybrids of L(1), a reaction with HgCl(2) in dmso as well as in dmf gave host-guest complexes, 1a and 1b, respectively, with the corresponding solvent of crystallization as the guests, while a reaction with HgI(2) gave open-frame network structures without any solvent of crystallization from both dmso and dmf (1c). However, reaction with HgBr(2) gave crystals of two different morphologies from each solvent dmso and dmf (1d-1f), which corresponds to the structures with and without solvent of crystallization that resemble the related structures formed by HgCl(2) and HgI(2), respectively. Three-dimensional structures of all the compounds were characterized by single-crystal X-ray diffraction methods. While 1a and 1b crystallize in triclinic P (1) over bar space groups 1a: a = 9.049(2), b = 13.646(4), c = 16.298(4) angstrom, a = 111.99(1), beta = 90.43(1), gamma = 101.57(1)degrees, Z = 2, V = 1820.6(8) angstrom(3), 1b: a = 8.9799(3), b = 13.611(5), c = 16.355(5) angstrom, a = 111.57(1), beta = 92.37(1), gamma = 101.07(1)degrees, Z = 2, V = 1810.05(11) angstrom(3) complexes 1c-1f crystallize into monoclinic space groups [1c: C2/c, a = 27.661(7), b = 18.821(4), c = 15.786(4) angstrom, beta = 113.13(1), Z = 4, V = 7558(3) angstrom(3), 1d: P2(1)/c, a = 17.950(5), b = 9.031(2), c = 22.200(6) angstrom, beta = 113.62(1), Z = 4, V = 3297.3(15) angstrom(3), 1e: C2/c, a = 26.753(15), b = 18.415(10), c = 14.940(7) angstrom, beta = 109.50(1), Z = 4, V = 6938(6) angstrom(3), 1f: P2(1)/n, a = 17.697(10), b = 9.224(5), c = 21.933(12) angstrom, beta = 112.50(1), Z = 4, V = 3308(3) angstrom(3)]. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: Biomass; dominant; Modelling; pyrolysis shrinkage

Solid-state structures of 4-carboxyphenylboronic acid and its hydrates - SeethaLekshmi, Nanappan; Pedireddi, Venkateswara Rao (Crystal Growth & Design, 2007)
Solid-state structures of 4-carboxyphenylboronic acid (1a) and its mono- and quarter-hydrates (1b and 1c, respectively) obtained by crystallization from different solvents, acetone, methanol, and 2-proponal, respectively, have been reported. In the anhydrous and monohydrate structures (1a and 1b), the H-atoms on the -B(OH)(2) functional group exist in syn-syn conformation, but syn-anti conformation was found in the quarter-hydrate structure. While 1a and 1b crystallize through interactions between -B(OH)(2) and -COOH groups (heteromeric), homomeric interactions of the functional groups (COOH center dot center dot center dot COOH and B(OH)(2)center dot center dot center dot B(OH)(2)) were observed in 1c. In addition, although similar interactions prevail in 1a and 1b, the latter crystallizes in a noncentrosymmetric space group Ccc2, registering itself as a unique structure with unusual catenation features with the aid of water molecules. However, 1a and 1c show many common features in the molecular arrangement in the crystal lattices with the formation of sheet structures.

Supramolecular architecture in some 4-halophenylboronic acids - Shimpi, Manishkumar R.; SeethaLekshmi, Nanappan; Pedireddi, Venkateswara Rao (Crystal Growth & Design, 2007)
Crystal structures of 4-chloro- and 4-bromophenylboronic acids (1 and 2) and hydrates of 2 and 4-iodophenylboronic acid in two different forms (2a, 3a, and 3b), which were characterized by single-crystal X-ray diffraction methods, are reported. In structures I and 2, -B(OH)2 forms a syn-anti conformation, but it exists in syn-syn as well as anti-anti conformations in the hydrated structures 2a, 3a, and 3b. In all the structures, the molecules are held together by O-H center dot center dot center dot O interactions formed by -B(OH)2 groups. The C-H center dot center dot center dot X (X = Cl, Br, and I) interactions play an important role in crystal packing. In 2, Br center dot center dot center dot Br interactions are also observed. Interestingly, all the three hydrates form similar types of three-dimensional structures with the formation of channels, which are occupied by water molecules. The two hydrates of 4-iodophenylboronic acid (3a and 3b) are distinguishable on the basis of O center dot center dot center dot O short contacts, with an identical host lattice of the boronic acid.